Whole-body vibration on leg muscles thermography and femoral resistive index of in adult healthy dogs. (February 2019) - Santos, Ivan; Rahal, Sheila; Santos, Amanda; Inamassu, Leticia; Rodrigues, Miriam; Tsunemi, Miriam; Mamprim, Maria; Rodrigues, Celso; Teixeira, Carlos; Sato, Thais
Abstract: This study aimed to assess the influence of WBV exercise on muscles by means of infrared thermography and on resistive index (RI) of the femoral artery. The hypothesis was that WBV exercise protocol will induce increase of the muscle activity detected through skin surface temperature change and decreased of RI with WBV exercise. Ten adult healthy medium dogs, were submitted to WBV session. Thermographic images were taken from regions of biceps femoris and vastus lateralis muscles. Triplex Doppler was used to assess RI of the femoral artery. Exams were performed before and immediately after WBV exercise sessions for five days, and RI of the femoral artery was evaluated 24 h after the last WBV session. There were no statistically significant differences between thermographic temperatures of regions of biceps femoris muscle and vastus lateralis muscle before and immediately after the WBV sessions. Significant differences were observed between the mean RI values before WBV sessions between day 1 and day 3, day 3 and day 5, and before and immediately after session on day 3; between before and immediately after session on day 2, day 3, day 4 and day 5; between before session between day 2 and day 6, day 3 and day 6, day 5 and day 6; and before and immediately after session on day 5. The WBV exercises during five uninterrupted days in adult healthy dogs do not alter significantly the skin temperatures over regions of biceps femoris and vastus lateralis muscles, and increase the femoral RI. Highlights: Skin temperatures of the leg muscle do not alter during five days of WBV exercise. Skin temperature of the biceps femoris and vastus lateralis muscles increased simultaneously. Resistive Index of femoral artery increased during WBV exercise. Peak systolic velocity increased between before and after WBV exercise